2015
DOI: 10.4103/0019-5049.160946
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomised, clinical study to compare the use of McGrath ® , Truview ® and Macintosh laryngoscopes for endotracheal intubation by novice and experienced Anaesthesiologists

Abstract: Background and Aims:Video laryngoscopy has been recommended as an alternative during difficult conventional direct laryngoscopy using the Macintosh blade (MAC). However, successful visualisation of the larynx and tracheal intubation using some of the indirect laryngoscopes or video laryngoscopes (VL) requires hand-eye coordination. We conducted this study to determine whether non-channel VLs are easy to use for novices and whether there is any association between expertise with MAC and ease of tracheal intubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…provides an anterior refraction of 42 thus provides better laryngeal 18 view.Agreeing with our study mean time for intubation was increased with8,12,14,17,[19][20][21][22][23][24] truview scope but few studies found equal time taken for 9-11,25…”
supporting
confidence: 61%
“…provides an anterior refraction of 42 thus provides better laryngeal 18 view.Agreeing with our study mean time for intubation was increased with8,12,14,17,[19][20][21][22][23][24] truview scope but few studies found equal time taken for 9-11,25…”
supporting
confidence: 61%
“…[2627] There is a definite learning curve for the successful use of a videolaryngoscope. [28] Anaesthesiologists should have access to a videolaryngoscope and must be trained to use it.…”
Section: Optimising Endotracheal Intubationmentioning
confidence: 99%
“…In a study by Bakshi et al 13 in which they compared the use of McGrath, Truview and Macintosh laryngoscopes for endotracheal intubation by novice and experienced anaesthesiologists and found that time to intubation was longer with the video laryngoscope than Macintosh in both NVL (novice to video laryngoscope) group and EXP (experienced in all) group. In many studies, video laryngoscope takes more time as compared to direct laryngoscope.…”
Section: Discussionmentioning
confidence: 99%